Kajian Historiografi Ibnu Al-Atsir dalam al-Kamil fi al-Tarikh - Zaahidah Aufaa; Ainun Nuriyah R.S; Ajid Hakim; Ajid Thohir (UPT Publikasi Ilmiah, 2025)
Islamic historiography constitutes an intellectual legacy that plays a vital role in shaping the identity and historical consciousness of the Muslim community. One of the key figures in this tradition is Ibn al-Athir (1160–1233 CE), best known for his monumental work, al-Kāmil fī al-Tārīkh. This work not only records historical events chronologically but also presents a narrative construction rich with theological, moral, and political dimensions. This study aims to examine Ibn al-Athir’s historiographical method in al-Kāmil, focusing on his writing approach, sources used, as well as his editorial and narrative interpretation strategies. Employing the historical research method (heuristics, criticism, interpretation, and historiography), this research draws on al-Kāmil fī al-Tārīkh (Dar al-Kutub al-‘Ilmiyyah edition) as its primary source, utilizing a historiographical approach. The study finds that Ibn al-Athir applied the principles of tadhkirah (remembrance), ṣaḥīḥ (authenticity), and tāmm (completeness) in his historical writing. Furthermore, the findings reveal a deliberate strategy of omission concerning politically and socially sensitive parts of the narrative. Thus, al-Kāmil fī al-Tārīkh emerges as a model of Islamic historical writing that combines factual accuracy with meaning-making, significantly contributing to the development of both classical and contemporary Islamic historiography. This work remains relevant as a primary source and as a critical object of study for understanding the dynamics of Islamic historical writing across eras. Through a deep understanding of Ibn al-Athir’s historiographical method, this study seeks to contribute to the advancement of contemporary Islamic historiography.